Interleukin-14 Prevents Cytarabine or Irradiation Induced Neutropenia via JAK/STAT3 Signaling - Xu, Shengnan; Ye, Chaoqiong; Wu, Zhihua; Wen, Chuying; Huang, Wenhui; Deng, Cong; Hua, Jiaye; Xie, Wei; Xiao, Min (Iranian journal of immunology, 2025)
Severe neutropenia significantly increases the risk of bacterial infections. Recent studies have shown that the cytokine interleukin 14 (IL-14) plays an important role in immune cells, but its potential role in neutropenia induced by cytarabine (ara-c) or irradiation is unclear. To investigate the role of IL-14 in ara-c or irradiation-induced neutropenia. Two neutropenia models were induced by ara-c or irradiation. Neutrophil count was confirmed through flow cytometry and routine blood tests. IL-14 was used to assess the impact on neutropenia. IL-14 expression was analyzed using qPCR, Western blotting and ELISA. A IL-14 receptor (IL-14R) knockout mice model was utilized to confirm the role of IL-14R/STAT3 signaling in vivo. The results indicated that IL-14 treatment promoted proliferation and increased neutrophil counts in both bone marrow and peripheral blood, while IL-14R knockout suppressed this process. Furthermore, the downstream molecule of IL-14R, STAT3, showed enhanced phosphorylation levels in the presence of IL-14. Finally, we explored the source of IL-14 in the bone marrow, and found that lymphocytes secreted the highest levels of IL-14. Serum levels of IL-14 were significantly reduced in patients after chemotherapy. These results indicate that IL-14 prevents ara-c or irradiation-induced neutropenia by regulating lymphocytes and activating the IL-14R/STAT3 pathway in neutrophils. This evidence suggests that IL-14 is a potent cytokine for treating ara-c or irradiation-induced neutropenia.